Current and future use of remdesivir in patients with COVID-19 - V. M. Tsvetov; K. B. Mirzaev; D. A. Sychev (Izdatelstvo OKI, 2020)
There are prerequisites for the use of remdesivir against SARS-CoV-2 in stationary conditions. Remdesivir is not registered in the Russian Federation. The preliminary results of randomized clinical trials on the efficacy of remission are contradictory.